2005
DOI: 10.1175/jhm412.1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Maximum, Mean, and Low Flows of Turkish Rivers

Abstract: In this study the existence of trend in maximum, mean, and low flows of Turkish rivers has been investigated. The data consisted of the daily mean flows of nearly 100 flow stations in 24 hydrological regions of Turkey. Trend analysis has been carried out using the parametric t test and nonparametric τ (Mann–Kendall) test. Both tests have been applied to annual maximum, mean, 1-day, and 7-day low flows. Trend existence was detected in the majority of rivers in western and southern Turkey and in some parts of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 22 publications
1
47
0
1
Order By: Relevance
“…Consequently, several studies of trends in observed series of flood events have been conducted at a national level in various European countries, from which the most recent studies involve the following: Austria (Blöschl et al, 2012;Villarini et al, 2012), Finland (Korhonen and Kuusisto, 2010), France (Renard et al, 2008;Giuntoli et al, 2012), Germany Bormann et al, 2011), Ireland (Murphy et al, 2013), Poland (Strupczewski et al, 2001;Kundzewicz et al, 2012), Portugal (Silva et al, 2012), Slovenia (Ulaga et al, 2008), Spain , Sweden (Lindström and Bergström, 2004), Turkey (Cigizoglu et al, 2005) and the United Kingdom (Hannaford and Marsh, 2008;Prosdocimi et al, 2014). Reviews of the results obtained in these studies have been published by Hall et al (2014) and Madsen et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several studies of trends in observed series of flood events have been conducted at a national level in various European countries, from which the most recent studies involve the following: Austria (Blöschl et al, 2012;Villarini et al, 2012), Finland (Korhonen and Kuusisto, 2010), France (Renard et al, 2008;Giuntoli et al, 2012), Germany Bormann et al, 2011), Ireland (Murphy et al, 2013), Poland (Strupczewski et al, 2001;Kundzewicz et al, 2012), Portugal (Silva et al, 2012), Slovenia (Ulaga et al, 2008), Spain , Sweden (Lindström and Bergström, 2004), Turkey (Cigizoglu et al, 2005) and the United Kingdom (Hannaford and Marsh, 2008;Prosdocimi et al, 2014). Reviews of the results obtained in these studies have been published by Hall et al (2014) and Madsen et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…[3] Numerous studies have attempted to detect trends in hydrological data in various parts of the world (Douglas et al [2000] in USA, Hisdal et al [2001] in Europe, Black and Burns [2002] in Scotland, Birsan et al [2005] in Switzerland, Cigizoglu et al [2005] in Turkey). Significant trends have been reported in some regions but could in most cases be related to natural climatic fluctuations (e.g., because of the influence of the North Atlantic Oscillation) rather than climate change (Robson [2002] and Hannaford and Marsh [2006] in the UK).…”
Section: Introductionmentioning
confidence: 99%
“…These trend lines indicate a decrease in the early summer rainfall while an increase is observed in the late summer rainfall over Gauteng. Trend analysis was done using the nonparametric Mann-Kendall test (Hcigizoglu et al, 2005). The downward trend in early summer rainfall has a confidence level of only 62% while the confidence level of the upward trend in late summer is 82%.…”
Section: Seasonal Rainfall Characteristics Over Gautengmentioning
confidence: 99%